1999
DOI: 10.1155/1999/386856
|View full text |Cite
|
Sign up to set email alerts
|

The Statistical Properties of Host Load

Abstract: Understanding how host load changes over time is instrumental in predicting the execution time of tasks or jobs, such as in dynamic load balancing and distributed soft real‐time systems. To improve this understanding, we collected week‐long, 1 Hz resolution traces of the Digital Unix 5 second exponential load average on over 35 different machines including production and research cluster machines, compute servers, and desktop workstations. Separate sets of traces were collected at two different times of the ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…In [10], Dinda analysed several statistical properties of host load data. In [7], Di et al also analysed some statistical properties of CPU host load data and demonstrated their probability distribution.…”
Section: Related Workmentioning
confidence: 99%
“…In [10], Dinda analysed several statistical properties of host load data. In [7], Di et al also analysed some statistical properties of CPU host load data and demonstrated their probability distribution.…”
Section: Related Workmentioning
confidence: 99%
“…[5][6] [7] and [21]). In our case, one very important factor that must be considered in choosing the prediction method is its overhead since the jobs of interest are relatively short lived.…”
Section: Methodsmentioning
confidence: 99%
“…For CPU-intensive jobs, the goal is to find the resource on which the given job can run fast. However, runtime does not only depend on the machine's CPU speed, but also is strongly related to the machine's load [7] [8]. Therefore, the following equations are used to estimate the job's execution on each machine by assuming that the current load of the machine does not change in a relatively short period of time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we describe and use the August 1997 set. A more detailed description of our analysis can be found in [8,9] and the traces themselves can be found on the web. 1 All of the hosts in the August 1997 set were DEC Alpha DUX machines, and they form four classes: Production Cluster, 13 hosts of the PSC's "Supercluster", including two front-end machines (axpfea, axpfeb), four interactive machines (axp0 through axp3), and seven batch machines); Research Cluster, eight machines in an experimental cluster in our lab (manchester-1 through manchester-8)); Compute servers, two high performance large memory machines used by our group as compute servers for simulations and the like (mojave and sahara); and Desktops, 15 desktop workstations owned by members of our research group (aphrodite through zeno).…”
Section: Statistical Properties Of Load Tracesmentioning
confidence: 99%